MENINGKATKAN HASIL BELAJAR LARI 100 METER MELALUI PERMAINAN GALAH HADANG - Eka Sapitri; Andika Triansyah; Fitriana Puspa Hidasari (Universitas Tanjungpura, 2021)
AbstractThe problems in this study are the low learning outcomes of the 100 meter run, the teacher is less innovative in teaching patterns, the lack of enthusiasm of students in participating in learning to run 100 meters, when the practice of running 100 meters the closer to the finish line the speed decreases, and does not hunch your shoulders. The purpose of this study was to find out that there was an increase in learning outcomes for running 100 meters through the gala hadang game for class VII students of SMPN 08 Satap Sengah Temila. The research method that I use is the participant Classroom Action Research (CAR). Planning is determining what actions will be taken to improve, enhance or change the desired behavior and attitudes. Implementation is an action that has been planned by the researcher as an effort to improve, increase or change the desired. Observation is observing the results carried out with tests. Reflection, namely the authors review, see, and consider the results of research from various criteria, based on data analysis and test results for each cycle there is an increase in learning outcomes of 100 meters through the gala hadang game, namely the average value in pre-cycle with the average value of students namely 51.3 and the percentage of classical completeness only reached 21%. Cycle I with an average value of 62.3 with a percentage of 46% classical completeness. Cycle II with an average value of 82.3 with a classical completeness percentage of 88%. The conclusion of this research is that with the action of Cycle II the learning outcomes of 100 meter running through the gala hadang game have met the criteria so that this action research is not continued.Keywords: Learning Outcomes, Running 100 Meters, Game of Gala Hadang.